2023
DOI: 10.3390/su15021108
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Load Transfer Behaviors of the Composite Foundation Reinforced by the Geosynthetic-Encased Stone Column

Abstract: An accurate description of the load transfer behaviors of the geosynthetic-encased stone column (GESC) is of great importance for revealing the bearing capacity of GESC. Static load tests and shake table model tests were performed to characterize the static and dynamic load transfer behaviors of the composite foundation reinforced by the GESC. Under static loading, static load tests were conducted on a fully geosynthetic-encased stone column (FGESC), partially geosynthetic-encased stone column (PGESC) and trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The lateral restraint force provided by geotextile can reduce the bulging deformation of stone column and the settlement of composite foundation. The stiffness of the geotextile can directly affect the size of the radial restraint force when the pile is deformed by bulging, so the stiffness of the geotextile is the key parameter to measure the strength of the GESC composite foundation [35]. Under the condition that other parameters are the same, different numerical models are established by changing the geotextile stiffness to study the influence of geotextile stiffness on the strength of composite foundation.…”
Section: Analysis Of Influencing Factorsmentioning
confidence: 99%
“…The lateral restraint force provided by geotextile can reduce the bulging deformation of stone column and the settlement of composite foundation. The stiffness of the geotextile can directly affect the size of the radial restraint force when the pile is deformed by bulging, so the stiffness of the geotextile is the key parameter to measure the strength of the GESC composite foundation [35]. Under the condition that other parameters are the same, different numerical models are established by changing the geotextile stiffness to study the influence of geotextile stiffness on the strength of composite foundation.…”
Section: Analysis Of Influencing Factorsmentioning
confidence: 99%
“…They found that the settlement of the floating column composite foundation was mainly affected by the depth improvement ratio. Wang et al [37][38][39] carried out a series of field tests and finite element numerical simulations to study the bearing characteristic of the GESC. They found that the GESC could effectively reduce the lateral displacement of the soil mass.…”
Section: Introductionmentioning
confidence: 99%